2009
DOI: 10.1111/j.1365-2133.2009.09248.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin abolishes sweating via impaired sweat gland responsiveness to exogenous acetylcholine

Abstract: Summary Background Botulinum toxin A (BTX) disrupts neurotransmitter release from cholinergic nerves. The effective duration of impaired sweat secretion with BTX is longer relative to that of impaired muscle contraction, suggesting different mechanisms in these tissues. Objectives The aim of this study was to test the hypothesis that BTX is capable of altering sweating by reducing the responsiveness of the sweat gland to acetylcholine. Methods BTX was injected into the dorsal forearm skin of healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…From our data we suggest that SNAP‐25 transporter proteins, which are the target for BTX‐A, require more time to regenerate than VAMP proteins, the target for BTX‐B. Recently, apart from the presynaptic target, effects of BTX‐A on the postsynaptic aquaporin 5 water channel proteins were suggested, implying functional inhibition of sweat glands by inhibiting water flux 18 . This effect might be a distinct effect for BTX‐A, as SNAP‐25, a SNARE protein, was found colocalized to vesicles containing aquaporin proteins in rat kidney 19 .…”
Section: Discussionmentioning
confidence: 76%
“…From our data we suggest that SNAP‐25 transporter proteins, which are the target for BTX‐A, require more time to regenerate than VAMP proteins, the target for BTX‐B. Recently, apart from the presynaptic target, effects of BTX‐A on the postsynaptic aquaporin 5 water channel proteins were suggested, implying functional inhibition of sweat glands by inhibiting water flux 18 . This effect might be a distinct effect for BTX‐A, as SNAP‐25, a SNARE protein, was found colocalized to vesicles containing aquaporin proteins in rat kidney 19 .…”
Section: Discussionmentioning
confidence: 76%
“…In addition, Shibasaki et al. 13 recently reported that the mechanism by which BT‐A inhibits sweating over a long period involves not only blocking of the release of acetylcholine from nerve terminals but also reduction of the reactivity of sweat glands to acetylcholine. Consequently, in severe cases, at least 90 U of BT‐A must be administrated to suppress the release of acetylcholine from nerve terminals and increase permeability to sweat gland tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Given that AQP proteins have been identified in human sweat glands, coupled with findings that botulinum toxin inhibits water permeability via AQP-dependent mechanisms (72), botulinum toxin, which is recognized to abolish sweating (38), may do so via pre- and post- cholinergic synaptic mechanisms; although botulinum toxin is considered primarily as a pre-synaptic inhibitor of neurotransmission. Recently, Shibasaki et al (86) found that local administration of botulinum toxin in human skin completely blocked the sweating response to exogenous acetylcholine, lending support to a post-synaptic mechanism by which botulinum toxin can abolish sweating. Future studies are warranted to identify the precise mechanism(s) by which botulinum toxin blocks sweating independent of inhibition of cholinergic neurotransmission.…”
Section: Neural Pathway From the Brain To Sweat Glandmentioning
confidence: 98%